Anti-NASH Drug Development Hitches a Lift on PPAR Agonism - Boeckmans, Joost (Cells, 2019)
Non-alcoholic fatty liver disease (NAFLD) affects one-third of the population worldwide, of which a substantial number of patients suffer from non-alcoholic steatohepatitis (NASH). NASH is a severe condition characterized by steatosis and concomitant liver inflammation and fibrosis, for which no drug is yet available. NAFLD is also generally conceived as the hepatic manifestation of the metabolic syndrome. Consequently, well-established drugs that are indicated for the treatment of type 2 diabetes and hyperlipidemia are thought to exert effects that alleviate the pathological features of NASH. One class of these drugs targets peroxisome proliferator-activated receptors (PPARs), which are nuclear receptors that play a regulatory role in lipid metabolism and inflammation. Therefore, PPARs are now also being investigated as potential anti-NASH druggable targets. In this paper, we review the mechanisms of action and physiological functions of PPARs and discuss the position of the different PPAR agonists in the therapeutic landscape of NASH. We particularly focus on the PPAR agonists currently under evaluation in clinical phase II and III trials. Preclinical strategies and how refinement and optimization may improve PPAR-targeted anti-NASH drug testing are also discussed. Finally, potential caveats related to PPAR agonism in anti-NASH therapy are stipulated.